Internalization of State Defense Values to Darussalam Modern Islamic Boarding School Student in West Bandung - Renaldo Benarrivo; Dadan Kurnia; Iing Nurdin; P.Y.M. Wibowo Ndaruhadi; Lukman Munawar Fauzi; Angga Nurdin Rachmat; Arlan Siddha (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This community service aims to internalize the values of state defense to the students of the Darussalam Modern Islamic Boarding School, West Bandung. It is carried out in three phases of activities, namely education and socialization, implementation and strengthening as well as intensive assistance from August to October 2021. The observations results of activities indicate a change in attitude which refers to the implementation of state defense values in daily activities as santri in an inclusive manner. This can be seen from the increasing understanding of the average students before the activity and also the reobservation carried out after the activity. Internalization of the state defense values is intended to provide religious understanding and nationalism and patriotism that can support each other in social life. The values of state defense that are highlighted in this activity include love for the homeland, awareness of the nation and state, loyalty to Pancasila as the state ideology, being willing to sacrifice for the nation and state, as well as the initial ability to defend the state. The internalization of these values is carried out by taking into account the background of the participants as a student. The combination of religious understanding which is supported by the values of nationalism and patriotism will be a good character for the students